(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the directions of material and energy flow connection of rivers with the environment are presented. In order to clarify the complex relations between the structure, function and dynamics of river basin landscapes, the river basin was analyzed into natural, biological and social structural systems.